Niger : Providing All Nigeriens with Food, Education and Health Car, A Demographic Perspective - World Bank (Washington, DC, 2012)
The analysis focuses on: (1) the study of population (development and impact on different sectors) and reproductive health issues, including the HIV/AIDS epidemic; (2) examination of institutional structures responsible for population and reproductive health issues; (3) the performance of the population program since the 1984 Mexico Conference, and during the 10 years since the 1994 International Conference on Population and Development in Cairo; (4) factors hindering or helping the development of population and family planning activities, including gender issues (for example, the Family Code and the strong resistance to its adoption); (5) specific recommendations for future activities; (6) the institutional and organizational structures needed for new and effective interventions; and (7) the strategic dissemination of the report's conclusions.